Zero defects through P-M analysis -A case study - Gnanavel, C; Saravanan, R; Chandrasekaran, M (International Journal of Engineering and Technology, 2018)
Chronic losses â€“ smaller, frequent deviations that gradually have been accepted as normal, live up to their name by resisting a wide variety of corrective measures taken in this regard. The persistence owed to reasons like failure to understand their nature and usage of ineffective approaches in dealing them. Tracking down their caused can be arduous as they rarely have just one cause, and conventional measures have become ineffective. This calls for evolution of new conceptual tools. In this paper P-M analysis, a rigorous improvement methodology that supports the pillars of TPM such as equipment improvement (KOBETSU KAIZEN), quality maintenance (HINSHITSU HOZEN) and plant maintenance have been applied for eliminating chronic losses. A typical illustration is provided through a case study conducted in a fastener manufacturing industry.Â